ON THE LEGAL QUALIFICATION OF THE ADOPTION OF AN ILLEGAL REGULATORY LEGAL ACT - LIPEN N.S (Legal Bulletin)
The article discusses various approaches to the legal assessment of the adoption of an illegal normative legal act - is it a lawful or illegal act. The relevance of the article’s problems is due to the importance of consistency and consistency of legislation, the legality of regulatory legal acts. This is a necessary condition for the rule of law and the rule of law. The main purpose of this work is to evaluate various approaches to the legal qualification of the adoption of an illegal regulatory legal act. The problems under consideration . The article analyzes approaches to the reasons for the adoption of illegal regulatory legal acts, as well as the possibility of bringing to legal responsibility for these actions. The methods used. The study was conducted on the basis of modern general scientific methodology. The main method was the formal dogmatic approach. Along with it, logical, systemic, sociological and other approaches were also used.